2016
DOI: 10.1002/2016jb012919
|View full text |Cite
|
Sign up to set email alerts
|

Offshore Southern California lithospheric velocity structure from noise cross‐correlation functions

Abstract: A new shear wave velocity model offshore Southern California is presented that images plate boundary deformation including both thickening and thinning of the crustal and mantle lithosphere at the westernmost edge of the North American continent. The Asthenospheric and Lithospheric Broadband Architecture from the California Offshore Region Experiment (ALBACORE) ocean bottom seismometer array, together with 65 stations of the onshore Southern California Seismic Network, is used to measure ambient noise correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 55 publications
0
34
1
Order By: Relevance
“…In a second step the velocity in offshore regions is calculated as vfalse(x,yfalse)=vcdfalse(x,yfalse)4,000, where v c is the 3.05 and 3.2 km/s for Rayleigh and Love waves, respectively, and d ( x , y ) is the spatially dependent bathymetry in meters with x and y being the spatial coordinates. The right‐hand side term reduces the velocity linearly with depth and at 4‐km depth the velocity is reduced by 1 km/s, which yields the observed Rayleigh wave phase velocity (Bowden et al, ). Love waves are assumed to be roughly 9% faster (Lin et al, ), which is in agreement with the above equation.…”
Section: Data and Preliminary Testingmentioning
confidence: 81%
See 3 more Smart Citations
“…In a second step the velocity in offshore regions is calculated as vfalse(x,yfalse)=vcdfalse(x,yfalse)4,000, where v c is the 3.05 and 3.2 km/s for Rayleigh and Love waves, respectively, and d ( x , y ) is the spatially dependent bathymetry in meters with x and y being the spatial coordinates. The right‐hand side term reduces the velocity linearly with depth and at 4‐km depth the velocity is reduced by 1 km/s, which yields the observed Rayleigh wave phase velocity (Bowden et al, ). Love waves are assumed to be roughly 9% faster (Lin et al, ), which is in agreement with the above equation.…”
Section: Data and Preliminary Testingmentioning
confidence: 81%
“…For secondary microseisms (8 s), where a large difference between the land and offshore phase velocity was observed (Bowden et al, ), the transition from oceanic to continental velocity can be significant and induce raypath bending. For this purpose a bathymetry‐dependent phase velocity is generated (in accordance with Bowden et al, ) and an example of the Love wave phase velocity map is shown in Figure a. Rayleigh and Love wave maps at 8 s are constructed in a two‐stage approach.…”
Section: Data and Preliminary Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…The data from the OBSs are used to distinguish among contrasting upper-mantle geodynamic scenarios that predict large-scale mantle flow patterns beneath western North America. In addition to anisotropy, seismic velocities are being obtained through inversion of dispersion curve data calculated from surface waves and cross correlation of ambient noise functions (Bowden et al 2016), as well as receiver function analysis (Reeves et al 2015).…”
Section: Introductionmentioning
confidence: 99%